The Flight from Reality in the Human Sciences - Shapiro, Ian (Book collections on Project MUSE., 2005)
In this captivating yet troubling book, Ian Shapiro offers a searing indictment of many influential practices in the social sciences and humanities today. Perhaps best known for his critique of rational choice theory, Shapiro expands his purview here. In discipline after discipline, he argues, scholars have fallen prey to inward-looking myopia that results from--and perpetuates--a flight from reality. In the method-driven academic culture we inhabit, argues Shapiro, researchers too often make display and refinement of their techniques the principal scholarly activity. The result is that they lose sight of the objects of their study. Pet theories and methodological blinders lead unwelcome facts to be ignored, sometimes not even perceived. The targets of Shapiro's critique include the law and economics movement, overzealous formal and statistical modeling, various reductive theories of human behavior, misguided conceptual analysis in political theory, and the Cambridge school of intellectual history.